Ensino de música para surdos: a prática educativa desenvolvida na ONG Instituto Inclusivo Sons do Silêncio - Nascimento, Tiago de Oliveira (2019)
The objective of the present research was to understand how the educational practice of the teaching of music for the Deaf occurs at NGO Instituto Inclusivo Sons do Silêncio, located in the city of Recife/PE. The specific objectives of the research were: to describe the functioning of the NGO structure; evidence of the role played by the teacher; verify the organization of the contents and the pedagogical objectives established in the classes; to investigate the methodological and evaluative procedures that were used in the teaching process and to highlight the pedagogical resources used in the classes. As a theoretical reference of the research, we use Zabala (1998), because this author discusses the concept of variables that intervene in educational processes, which was pertinent to the study. As a secondary reference, we use authors who discuss the teaching of music for the Deaf. The nature of the research was the qualitative approach and the strategy used was the case study. The data collected were the reports of the semistructured interview with the teacher responsible and the descriptions of the observations of his practice. Content analysis based on Bardin (2018) and Moraes (1999) was the analysis procedure used in the research. Based on the research results, we conclude that the educational practice of the music teacher of the Instituto Inclusivo Sons do Silêncio occurs in a constructivist perspective, where the Deaf student is an active subject of the learning process. The teacher acts as an agent of social transformation and his methodology Casa Inclusiva is used for the administration of lessons, that occur through the exploration of sound vibrations and the visual aspect, but still valuing the teaching of traditional music. The contents taught and the evaluation procedure dialogue and cooperate to achieve the pedagogical goals established in the classes, which is to prepare the students to play songs, to form a repertoire, and finally to be able to participate in the first philharmonic band of Brazil with focus in the deaf person